Implementación de un deshidratador para semillas de cacao mediante el uso de colectores solares - Cedeño Paladines, Byron Abel (2019)
At the present project the implementation of a dehydrator for cocoa seeds through the use of flat solar collectors was carried out, due to grain dehydration process and economic income of the producer as result of the humid product sales , flat solar collectors with continuous roofs when they receive solar radiation they store energy in heat way, which one can be transported by injecting a mass flow from air thanks to the heat transfer by forced convection, the increase of the thermal collector efficiency thanks square, triangular and hexagonal discontinuous roofs with respect to the continuous roof flat collectors allowed to improve the efficiency with a difference of 10.99% for the hexagonal roofs, of 14.26% for the square roofs and of the 0.6 % for triangular roofs, this is related to optimization process of power supply, being the square roof which increases the collector performance on 43.8%, with the most efficient time of the dehydration process in 33.34% and consequently increasing 0.41 dollars per kilogram of cocoa bean producer incomes and apliying the established objectives on the technological proposal.